Term Abdominal Pregnancy Revealed by Amnioperitoneum in Rural Area - Henri Donald Mutarambirwa; Bruno Kenfack; Jovanny Tsuala Fouogue (Case Reports in Obstetrics and Gynecology)
Abdominal pregnancy (AP) accounts for 1% of ectopic implantations. In sub-Saharan Africa, the high prevalence of sexually transmitted infections explains the increasing frequency of this pathology. In Cameroon it rose from 1/10000 deliveries (1995) to 3.3/10000 (2015). Authors herein report a case of a viable abdominal pregnancy discovered at term during emergency laparotomy for suspected uterine rupture. The 24-year-old G2P0 patient was HIV-positive, under antiretrovirals, though AP exceptionally occurs in HIV patients. She did only two antenatal consultations: her main complaint was abdominal pain but five echographies concluded to normal intrauterine pregnancy. Findings at laparotomy were as follows: amnioperitoneum, a live female baby weighing 3.4 kilogrammes without deformities and a placenta deeply inserted on the uterine fundus. Removal of the placenta triggered massive bleeding (2400 milliliters) with shock managed with a tourniquet on the lower uterine segment and fluid resuscitation. Outcome was favourable for the mother and child. Prevention of vertical transmission of HIV was successful with antiretroviral therapy.